Map Design Evaluation for Mobile Display - Dillemuth, Julie (Cartography and geographic information science, 2005)
How to effectively represent spatial information on handheld mobile devices is a key question, given the increasing use of personal digital assistants (PDAs) and cell phones concurrent with the development of location-based services. The mobile use of digital maps on small displays presents new capabilities and challenges that differ from using paper maps in a mobile setting or viewing digital maps on a desktop computer. This research addresses these issues through a study that evaluated maps on a mobile device used for a field-based navigation task. Map representations at two levels of generalization were compared by analyzing subject performance in a pedestrian route-following task, in which a handheld computer was used as a navigation aid. Subject time and accuracy as well as interaction with the mobile device during the task were measured. The results carry implications for map design for small, mobile displays and identify factors that affect the use of maps while moving. Maps are and will increasingly be used on small displays in mobile contexts for a variety of purposes and in many different environments. The requirements and preferences of mobile users, as well as how these maps are used in different contexts, must be understood in order to inform more effective designs.